An Assessment of Environmental Effects of the 2005 Mexican Automotive Decree - Stanchfield, Paul R.; Skartvedt, Brooke M.; Magua, James W.; Dullin, Jacqueline; DallAsta, Roberto A. (My University, 2006)
The authors examine the environmental effects of Mexican President Vicente Fox's 2005 Automotive Decree which allows the importation of 10- to 15-year-old used vehicles to Mexico. The authors focus on the air pollution effects in Mexican border-states resulting from the increased vehicle flow and discuss whether the decree is a net benefit or detriment to the environment. Based on their findings, the authors recommend policy options to decrease vehicle emissions in the border region.
For PA 860: Public Affairs Workshop, International Issues